THE BEST METHOD TO PREVENT NON-PERFORMING LOANS: TEMPORARY STOPPING DISTRIBUTION OF BANTEN MICRO CREDIT BY PT BPR SERANG (PERSERODA) KASEMEN BRANCH - Latif, Abdul; Hardiyanti, Siti Epa (Management Science Research Journal, 2023)
PT BPR Serang (Perseroda) Kasemen Branch is one of the banks whose share ownership is partially owned by the local government of Serang Regency and has the main activity in the form of lending aimed at the community in the Serang Regency area. One of the credit products provided by PT BPR Serang (Perseroda) Kasemen Branch is the Banten Microcredit. The credit is a loan aimed at micro, small and medium enterprises to increase the business capital of these business actors. During the Covid-19 pandemic, PT BPR Serang (Perseroda) Kasemen Branch has temporary stopping micro-credit to minimize credit risk during the Covid-19 pandemic. This research conducts a case study of PT BPR Serang (Perseroda) Kasemen Branch and finds out whether it is true that the termination of microcredit can minimize credit risk or even have a negative impact on the business operations of Serang (Perseroda) Kasemen Branch